The Effects of Working While in School: Evidence from Uruguayan Lotteries - Thomas Le Barbanchon; Diego Ubfal; Federico Araya (Institute of Labor Economics (IZA), 2020)
Shall we encourage students to work while in school? We provide evidence by leveraging a one-year work-study program that randomizes job offers among students in Uruguay. Using social security data matched to over 120,000 applicants, we estimate an increase of 9% in earnings and of 2 percentage points in enrollment over the four post-program years for treated youth. Survey data indicate that enrolled participants reduce study time, but this does not translate into lower grades. Students mainly substitute leisure and household chores with work. The earnings effect is related to the work experience and the transferability of skills acquired in program jobs.
Keywords: J08; J22; J24; I21; I28; 330; student employment; randomized lottery